Advances in immunology. - Dixon, Frank J. (Frank James), 1920-2008 (Advances in immunology., 1995)
This volume highlights the latest reviews of mechanisms and actions of the immune system and the host response to infection and inflammation. Key Features * Covers cytokine functioning as influenced by the Janus protein tyrosine kinase family * Explores immunodeficiencies, including: * Immunoglobulin deficiencies and B cells development * Glycosyl Phosphatidylinositol (GPI)-anchor and Paroxysmal Nocturnal Hemoglobinuria (PNH) * Investigates the links molecular pathology established between deficiencies in GPI-anchor synthesis and PNH * Includes the use of Multiple Antigen Peptides (MAPs) to induce protective immune response * Offers a timely update on Eosinophils' role in disease * Covers histology of Germinal center reaction of a spleen twelve days after primary immunization * Includes new research on cytotoxic T-lymphocytes * Presents the multiple roles of Nitric oxide (NO) in the inflammatory response.